CHARACTERISTICS OF GOOD ENGLISH TEACHERS BASED ON THE PERCEPTION OF THE STUDENTS FROM DIFFERENT LEARNING STYLES AND PERSONALITIES - Sriyuliyana, Fausiah (Qalam : Jurnal Ilmu Kependidikan, 2018)
The Â research aims are (i) Identifying the characteristics of good English teachers in SMAN 3 Sinjai Selatan. (ii) Knowing the characteristics of good English teacher based on the studentsâ€™ learning style. (iii) Knowing the characteristics of good English teacher based on the studentsâ€™ personality. This research was done by using a qualitative approach. The data were collected by using two instruments i.e. questionnaires and in depth interview. The results of this study reveal that (i) The characteristics of good English teacher based on the studentsâ€™ perception in SMAN 3 Sinjai Selatan are categorized into four different categories, namely proficiency, pedagogical (both conceptual and practical), socio-affective and psychological aspect. The last category was the additional category in which age included in and differently from the work of Gi and Â Hyo (2006) that only specified three categories, namely proficiency, pedagogical and socio-affective skills. (ii) In general, the characteristics of good English teacher based on the studentsâ€™ learning style are dominantly in pedagogical aspect. Visual learners want English teacher who can keep the studentsâ€™ focus and concentration in their learning; auditory learners expect English teacher who can engage the studentsâ€™ motivation and interest toward learning English; and haptic learners propose the English teacher who concerns on the process rather than the achievement of the students in learning. (iii) The characteristics of good English teacher proposed by high school students based on their personality are dominantly on the teacherâ€™s pedagogical and socio-affective aspects. Only a few ideas of the students that concern on the teacherâ€™s proficiency and psychological aspect.